SUCCESSES AND FAILURES OF FOREIGN POLICY OF NICHOLAS I (ACCORDING THE MEMORIES OF CONTEMPORARIES) - E. P. Kudryavtseva (Vestnik MGIMO-Universiteta)
The article is devoted to the successes and failures of Russian foreign policy during the reign of Nicholas I. The key sources of the research are memoires of people who were in close attendance on the Emperor, foreign diplomats, travelers and members of European royal families. They noted some traits of his personality, political views, commitment to order and military service. They left valuable remembrance about all important foreign-policy cases the Russian Emperor was involved in: Russo-Turkish War (1828–1829), contacts with the Balkan states, Eastern Question within the framework of the Russian role in the course of events of the Egyptian–Ottoman War (1832–1833); hostility against French Revolutions and contacts with the allied Prussia and the Austrian Empire. These reminiscences make it possible to discover the attitude of Nicolas I to the European revolutions in the first half of XIX-th and illegitimate monarchs in Europe. They let us track the way the foreign policy influenced the Russian inner policy. The sources are very informative to explain the different steps of Russian foreign policy in the most important points – in the Middle East, in Europe and in Turkey.